2010
DOI: 10.1021/ja103262m
|View full text |Cite
|
Sign up to set email alerts
|

Transannular Disulfide Formation in Gliotoxin Biosynthesis and Its Role in Self-Resistance of the Human Pathogen Aspergillus fumigatus

Abstract: Gliotoxin (1), the infamous representative of the group of epipolythiodioxopiperazines (ETPs), is a virulence factor of the human pathogenic fungus Aspergillus fumigatus. The unique redox-sensitive transannular disulfide bridge is critical for deleterious effects caused by redox cycling and protein conjugation in the host. Through a combination of genetic, biochemical, and chemical analyses, we found that 1 results from GliT-mediated oxidation of the corresponding dithiol. In vitro studies using purified GliT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 131 publications
(187 citation statements)
references
References 42 publications
4
172
0
7
Order By: Relevance
“…It has been demonstrated that A. fumigatus is capable of self protection against gliotoxin, and that deletion of gliT significantly increased strain sensitivity to exogenous gliotoxin (32,33). Both ⌬gliK mutants were also significantly more sensitive to gliotoxin (P Ͻ 0.001), and a reduced growth rate was seen at all time points, with the greatest difference in growth seen at 72 h (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It has been demonstrated that A. fumigatus is capable of self protection against gliotoxin, and that deletion of gliT significantly increased strain sensitivity to exogenous gliotoxin (32,33). Both ⌬gliK mutants were also significantly more sensitive to gliotoxin (P Ͻ 0.001), and a reduced growth rate was seen at all time points, with the greatest difference in growth seen at 72 h (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Although a statistically significant difference in growth rates was observed between A. fumigatus wild-type and respective ⌬gliK strains, addition of gliotoxin did not completely suppress growth of ⌬gliK 46645 and ⌬gliK 26933 mutants, even at high concentrations of gliotoxin (20 g/ml). Thus, observed gliotoxin sensitivity was less apparent than that previously encountered for A. fumigatus ⌬gliT (32,33). Hence, we hypothesized that although gliK plays a role in self protection against gliotoxin, it is more likely that any metabolite (biosynthetic intermediate or shunt metabolite) produced consequent to gliK deletion mediates sensitivity to exogenous gliotoxin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly at 6 h GT exposure, 26 GHs showed increased abundance compared to one that was detectable at lower levels (Table 3). In addition, peptidase abundance showed high levels of dysregulation, whereby 16 showed increased and 4 decreased abundance (at 3 h) and 18 increased with 8 showing reduced abundance at 6 h post-GT exposure ( Table 4). The majority of these degradative enzymes were observed at both timepoints (57.6% GHs and 43.8% peptidases).…”
Section: Hydrolytic Enzyme Abundance Is Increased In Response To Gtmentioning
confidence: 99%
“…The recombinant GliT protein (AFUA_6G09740) was produced in E. coli and purified as described (26). The open reading frames of the genes scw4 (AFUA_6G12380), aspf3 (AFUA_6G02280), shm2 (AFUA_3G09320), cpcB (AFUA_4G13170), and aspf22 (AFUA_6G06770) were amplified from ATCC46645 cDNA and cloned into the expression vector pET43.1H6 for recombinant expression as His-tagged proteins.…”
Section: Generation Of Recombinant a Fumigatus Proteinsmentioning
confidence: 99%